2016
DOI: 10.1080/09637486.2016.1207061
|View full text |Cite
|
Sign up to set email alerts
|

Dried fruit and dental health

Abstract: A comprehensive review of the literature has found that the common perceptions that dried fruits are "sticky", adhere to teeth, and are detrimental to dental health on account of their sugar content are based on weak evidence. There is a lack of good quality scientific data to support restrictive advice for dried fruit intake on the basis of dental health parameters and further research is required. A number of potentially positive attributes for dental health, such as the need to chew dried fruits which encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In juices, the sugars present have been released from the cellular structure and are therefore considered to be ‘free sugars’, but the free sugars content of dried fruit is considered to be zero. However, chewing presumably releases sugars within cells into the mouth, and it is not clear when or if these are considered ‘free’ (Sadler ).…”
Section: Sugars Content Of Dried Fruitmentioning
confidence: 99%
See 4 more Smart Citations
“…In juices, the sugars present have been released from the cellular structure and are therefore considered to be ‘free sugars’, but the free sugars content of dried fruit is considered to be zero. However, chewing presumably releases sugars within cells into the mouth, and it is not clear when or if these are considered ‘free’ (Sadler ).…”
Section: Sugars Content Of Dried Fruitmentioning
confidence: 99%
“…). A recent review of the evidence on dried fruit and dental health found a lack of good quality studies to support the advice to restrict intake to mealtimes (Sadler ). Relevant endpoints in studies assessing effects of foods on dental health are dental caries per se , net demineralisation and acidogenicity (measured by interproximal plaque pH, acid production or plaque pH per se ).…”
Section: Summary Of the Evidence On Dried Fruit And Dental Healthmentioning
confidence: 99%
See 3 more Smart Citations